Ecology can inform genetics: Disassortative mating contributes to MHC polymorphism in Leach's storm‐petrels (Oceanodroma leucorhoa). Issue 16 (16th August 2018) - Hoover, Brian; Alcaide, Miguel; Jennings, Sarah; Sin, Simon Yung Wa; Edwards, Scott V.; Nevitt, Gabrielle A.
Abstract: Studies of MHC‐based mate choice in wild populations often test hypotheses on species exhibiting female choice and male–male competition, which reflects the general prevalence of females as the choosy sex in natural systems. Here, we examined mutual mate‐choice patterns in a small burrow‐nesting seabird, the Leach's storm‐petrel ( Oceanodroma leucorhoa ), using the major histocompatibility complex (MHC). The life history and ecology of this species are extreme: both partners work together to fledge a single chick during the breeding season, a task that requires regularly travelling hundreds of kilometres to and from foraging grounds over a 6‐ to 8‐week provisioning period. Using a 5‐year data set unprecedented for this species ( n = 1078 adults and 925 chicks), we found a positive relationship between variation in the likelihood of female reproductive success and heterozygosity at Ocle‐DAB2, a MHC class IIB locus. Contrary to previous reports rejecting disassortative mating as a mechanism for maintaining genetic polymorphism in this species, here we show that males make significant disassortative mate‐choice decisions. Variability in female reproductive success suggests that the most common homozygous females (Ocle‐DAB2*01/Ocle‐DAB2*01) may be physiologically disadvantaged and, therefore, less preferred as lifelong partners for choosy males. The results from this study support the role of mate choice in maintaining high levels of MHC variability in a wild seabird species and highlight the need to incorporate a broader ecological framework and sufficient sample sizes into studies of MHC‐based mating patterns in wild populations in general.